Design of fuzzy controller using schema coevolutionary algorithm. - Kwee-Bo Sim
Researches on the design of the optimal fuzzy controller have been carried out for many years. Various approaches to fuzzy modeling have been proposed. In this paper, we introduce a novel algorithm, schema coevolutionary algorithm, for fuzzy modeling. We demonstrate the schema coevolutionary algorithm and compare it with other similar coevolutionary algorithms: virus-evolutionary genetic algorithm and coevolution of Handa. Then, we apply it to design the optimal fuzzy controller. The fuzzy controller is used to control the mobile robot and optimized by the schema coevolutionary algorithm. We verify the efficacy of this algorithm through the experiment and comparison with other algorithms.
Keywords: Fuzzy controller design; Fuzzy modelling; Mobile robots; Optimal controller; Schema coevolutionary algorithm; Virus-evolutionary genetic algorithm